(untitled) - McDonald, Michael (New York, 2002)
A fresh perspective on predicting the market. The experience of Wall Street investment manager and analyst Michael McDonald offers a new perspective on how to navigate the turbulent ups and downs of the markets. His innovative approach to the stock market teaches investors how to use new investment strategies intended to replace the "buy and hold forever" strategies of yesterday. McDonald discusses what a "trading range" market is-a roller-coaster ride in which the market will neither gain nor lose much ground-and guides readers through this market with his proven investment strategies. This book provides an understandable way to make sense of the unpredictable stock market, taking into account more complex theories, including chaos and contrarian approaches. Along with his expert advice, McDonald presents four investing paradoxes that will help investors make smarter decisions now and predict where the market is heading, using his proven theories.
Keywords: Stock price forecasting,Investment analysis,Dự báo giá cổ phần,Phân tích đầu tư